¿Son convincentes los argumentos de Epicuro y Lucrecio para rechazar el temor a la muerte? - Rosell, Sergi (2022)
The present paper attempts to reconstruct and assess the main Epicurean arguments against the idea that death is an evil for the one who dies.In order to fight against the life anguished by the fear of death, Epicurus and Lucretius deploy a series of arguments aimed at showing the irrationality or thelack of justification of this fear. Although I share the thesis according to which an eudaimonic life entails the acceptance of our mortal nature, I suggest, however, that this does not force us to embrace the much more radical thesis according to which “death is nothing for us”. Particularly, the paper argues that the discussedarguments invalidate the fear of the fact itself of being dead, but not other fears related to the fact of not carrying on living.